The Effect of Life Expectancy on Aggression and Generativity: A Life History Perspective - Curtis S. Dunkel; Eugene Mathes; Dennis R. Papini (Evolutionary Psychology, 2010)
Following a model that is inclusive of both dispositional and situational influences on life-history behaviors and attitudes, the effect of life expectancies on aggression and generativity was examined. Consistent with the hypotheses it was found that shorter life expectancies led to an increase in the desire to aggress and a decrease in the desire to engage in generative behaviors. The results are discussed in terms of how life history theory can be used to frame research on person-situation interactions.